Palladium‐Catalyzed One‐Pot Consecutive Amination and Sonogashira Coupling for Selective Synthesis of 2‐Alkynylanilines. Issue 14 (25th September 2015) - Pan, Shanfei; Ma, Xueji; Zhong, Danni; Chen, Wanzhi; Liu, Miaochang; Wu, Huayue
Abstract: An efficient catalytic approach to the synthesis of N, N ‐dialkyl‐2‐alkynylanilines was developed by using Pd‐catalyzed norbornene‐mediated three‐component reactions of haloarenes, alkoxyamines (RO‐NR2 ), and alkynes. The procedure forms one CN bond and one CC bond efficiently in a one‐pot manner from readily available starting materials. A number of 2‐alkynylanilines with a broad range of functional groups were afforded in good to excellent yields. Abstract :